Ion irradiation-induced sputtering and surface modification of BN films prepared by a reactive plasma-assisted coating technique. (1st July 2022) - Matsuda, T.; Hamano, T.; Asamoto, Y.; Noma, M.; Yamashita, M.; Hasegawa, S.; Urabe, K.; Eriguchi, K.
Abstract: Boron nitride (BN) films with a wide variety of nano-network structures ( sp 2 and sp 3 bonds) were prepared using a reactive plasma-assisted coating technique, and their sputtering behavior was investigated. Fourier transform infrared spectroscopy (FTIR) and nanoindentation analyses confirmed the presence of sp 2 - and sp 3 -bonded phases. Subsequently, the thickness change after plasma exposure was studied for various BN films. The sputtered depth of the prepared BN films after plasma exposure was shallower than that of the SiO2 films. While no clear change was observed in the FTIR spectra, the leakage current and dielectric constant changed significantly owing to the surface modification during plasma exposure. The modified layer underneath the sputtered surface contained local defects that acted as carrier trapping or hopping sites. Sputtering behavior analysis, in combination with electrical measurements, is a useful methodology for designing a wide variety of BN films.